2000
DOI: 10.1128/jvi.74.5.2107-2120.2000
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine, a Specific Inhibitor of Cellular Cyclin-Dependent Kinases, Inhibits Herpes Simplex Virus DNA Synthesis in the Presence of Viral Early Proteins

Abstract: We have previously shown that two inhibitors specific for cellular cyclin-dependent kinases (cdks), Roscovitine (Rosco) and Olomoucine (Olo), block the replication of herpes simplex virus (HSV). Based on these results, we demonstrated that HSV replication requires cellular cdks that are sensitive to these drugs (L. M. Schang, J. Phillips, and P. A. Schaffer. J. Virol. 72:5626-5637, 1998). We further established that at least two distinct steps in the viral replication cycle require cdks: transcription of immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
3
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 80 publications
5
74
3
3
Order By: Relevance
“…61 A building block found in all three supramolecular structures is the R2 2 (9) heterosynthon based on double H bonds between a protonated Hoogsteen site and a carboxylate group. Besides the R2 2 (9) heterosynthon, 1 contains an R2 2 (8) …”
Section: 9(2)° 21 ) While the C(4)-n(9)-c(8) C(2)-n(3)-c(4) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…61 A building block found in all three supramolecular structures is the R2 2 (9) heterosynthon based on double H bonds between a protonated Hoogsteen site and a carboxylate group. Besides the R2 2 (9) heterosynthon, 1 contains an R2 2 (8) …”
Section: 9(2)° 21 ) While the C(4)-n(9)-c(8) C(2)-n(3)-c(4) Andmentioning
confidence: 99%
“…1-3 N 6 -furfurylaminopurine (kinetin) is a representative of naturally occurring adenine-type cytokinins, a class of plant growth factors that can also act as inhibitors of certain human protein kinases. 4,5 Some kinetin analogues such as olomoucine 6,7 and roscovitine 8 selectively inhibit cyclindependent kinases, which play an essential role in the regulation of the cell division cycle, 6,9 and therefore are potent anticancer agents. Roscovitine, for example, has entered clinical trials for the treatment of non-small cell lung cancer and leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…These observations could appear paradoxical in as much as recent studies have shown that replication of Herpes Simplex Virus (and other large DNA viruses) requires cellular proteins including CDKs. [14][15][16][17][18][19][20][21] One of the potential mechanisms accounting for these adverse effects might be the negative regulation of TLR signaling pathways by CDKi and/or GSK3β inhibition, as suggested by previous in vitro studies.…”
Section: Abstract: Tlr Dendritic Cells Cancer Herpes Cdk Inhibitorsmentioning
confidence: 99%
“…Tumor associated-mutations deregulate distinct CDKcyclin complexes causing unscheduled proliferation. Deregulation of CDK4 and CDK6 activities have been implicated in a variety of human malignancies, CDK4 being hyperactive in epithelial a 4-week cycle, i.e., with treatment on days 1, 8, 15 followed by a 2-week resting period (day [16][17][18][19][20][21][22][23][24][25][26][27][28] (Fig. 1A).…”
Section: Abstract: Tlr Dendritic Cells Cancer Herpes Cdk Inhibitorsmentioning
confidence: 99%
“…In human cell lines examined, roscovitine arrests cells in the G 1 and the G 2 /M phases of the cell cycle Pippin et al, 1997;Alessi et al, 1998), inhibits DNA synthesis (Yakisich et al, 1999;Schang et al, 2000), causes nucleolar fragmentation (David-Pfeuty, 1999), induces apoptosis (Mgbonyebi et al, 1999;Atienza et al, 2000), and inhibits apoptosis (Maas et al, 1998;Choi et al, 1999;Hiromura et al, 1999;Padmanabhan et al, 1999;Giardina and Beart, 2002).…”
Section: Introductionmentioning
confidence: 99%